2021
DOI: 10.1038/s41467-020-20723-x
|View full text |Cite
|
Sign up to set email alerts
|

Boosting anti-PD-1 therapy with metformin-loaded macrophage-derived microparticles

Abstract: The main challenges for programmed cell death 1(PD-1)/PD-1 ligand (PD-L1) checkpoint blockade lie in a lack of sufficient T cell infiltration, tumor immunosuppressive microenvironment, and the inadequate tumor accumulation and penetration of anti-PD-1/PD-L1 antibody. Resetting tumor-associated macrophages (TAMs) is a promising strategy to enhance T-cell antitumor immunity and ameliorate tumor immunosuppression. Here, mannose-modified macrophage-derived microparticles (Man-MPs) loading metformin (Met@Man-MPs) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
174
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(195 citation statements)
references
References 62 publications
4
174
0
Order By: Relevance
“…Similarly, Zhang et al described a nanocarrier-based delivery system for loading interferon regulatory factor 5 and IKKβ to TAMs to reverse M2-like TAMs into M1-like phenotypes without causing in vivo systemic toxicity [ 122 ]. In addition, Wei et al treated macrophages with mannose (Man)-modified macrophage-derived MPs, which are carriers for the targeted delivery of metformin (called Met@Man-MPs) to M2-like TAMs [ 123 ]. They showed that Met@Man-MPs efficiently reset TAMs toward the M1 phenotype to inhibit tumor growth.…”
Section: Immunotherapy and Tam-targeted Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Zhang et al described a nanocarrier-based delivery system for loading interferon regulatory factor 5 and IKKβ to TAMs to reverse M2-like TAMs into M1-like phenotypes without causing in vivo systemic toxicity [ 122 ]. In addition, Wei et al treated macrophages with mannose (Man)-modified macrophage-derived MPs, which are carriers for the targeted delivery of metformin (called Met@Man-MPs) to M2-like TAMs [ 123 ]. They showed that Met@Man-MPs efficiently reset TAMs toward the M1 phenotype to inhibit tumor growth.…”
Section: Immunotherapy and Tam-targeted Therapymentioning
confidence: 99%
“…They showed that Met@Man-MPs efficiently reset TAMs toward the M1 phenotype to inhibit tumor growth. Met@Man-MPs significantly improved the tumor immunosuppressive microenvironment and enhanced CD8+ T cell infiltration into the tumor interior by restoring macrophage-induced recruitment of CD8+ T cells and Man-MP-induced tumor ECM degradation because macrophages express matrix metalloproteinases (MMP) [ 123 ]. In addition, the utilization of normal MSCs to modulate TAM polarization is another promising therapeutic strategy.…”
Section: Immunotherapy and Tam-targeted Therapymentioning
confidence: 99%
“…However, the anti-tumor effect was insufficient for further evaluation, which might be because most recruited patients were resistant to the PD-1 antibody ( 79 ). Recently, mannose-modified macrophage-derived microparticles loaded with metformin have been developed to reprogram M2 to M1 macrophages, which can synergistically enhance anti-PD-1 therapy ( 80 ).…”
Section: Macrophage Reprogramming and Pd-l1/pd-1 Blockade In Cancer Therapymentioning
confidence: 99%
“…A similar result was seen in IL-4-stimulated RAW264.7 cells, murine bone marrow-derived macrophages, THP-1-originated macrophages, and human peripheral blood monocyte-derived macrophages, where mannose-modified, macrophage-derived microparticles loaded with metformin converted the M2 phenotype toward M1. In this study, such microparticles loaded with metformin were also effective in an animal model to reprogram the tumor immune microenvironment [ 139 ]. In addition, metformin was reported to act on the cancer cell to reduce the M2 polarization of the tumor-associated macrophage.…”
Section: Metformin On the Immune Population That May Indirectly Inhibit Nash-related Hcc Developmentmentioning
confidence: 99%